Plants as Biofactories: Postharvest Stress-Induced Accumulation of Phenolic Compounds and Glucosinolates in Broccoli Subjected to Wounding Stress and Exogenous Phytohormones - Villarreal-García, Daniel; Nair, Vimal; Cisneros-Zevallos, Luis; Jacobo-Velázquez, Daniel A. (Frontiers in Plant Science, 2016)
Broccoli contains high levels of bioactive molecules and is considered a functional food. In this study, postharvest treatments to enhance the concentration of glucosinolates and phenolic compounds were evaluated. Broccoli whole heads were wounded to obtain florets and wounded florets (florets cut into four even pieces) and stored for 24 h at 20 ºC with or without exogenous ethylene (ET, 1000 ppm) or methyl jasmonate (MeJA, 250 ppm). Whole heads were used as a control for wounding treatments. Regarding glucosinolate accumulation, ET selectively induced the 4-hydroxylation of glucobrassicin in whole heads, resulting in ~223% higher 4-hydroxyglucobrassicin than time 0 h samples. Additionally, glucoraphanin was increased by ~53% in whole heads treated with ET, while neoglucobrassicin was greatly accumulated in wounded florets treated with ET or MeJA, showing increases of ~193% and ~286%, respectively. On the other hand, although only whole heads stored without phytohormones showed higher concentrations of phenolic compounds, which was reflected in ~33%, ~30%, and 46% higher levels of 1,2,2-trisinapoylgentiobose, 1,2-diferulolylgentiobiose, and 1,2-disinapoyl-2-ferulolylgentiobiose, respectively; broccoli florets stored under air control conditions showed enhanced concentrations of 3-O-caffeoylquinic acid, 1,2-disinapoylgentiobiose, and 1,2-disinapoyl-2-ferulolylgentiobiose (~22%, ~185%, and ~65% more, respectively). However, exogenous ET and MeJA impeded individual phenolics accumulation. Results allowed the elucidation of simple and effective postharvest treatment to enhance the content of individual glucosinolates and phenolic compounds in broccoli. The stressed-broccoli tissue could be subjected to downstream processing in order to extract and purify bioactive molecules with applications in the dietary supplements, agrochemical and cosmetics markets.